Ethical Implications of Artificial Intelligence Implementation in Elementary Schools: A Systematic Review - Ani Nuryani; Oktaviani Adhi Suciptaningsih; Ade Eka Anggraini (Journal of Innovation and Research in Primary Education, 2026)
Artificial Intelligence (AI) implementation in elementary education presents both transformative opportunities and ethical challenges that require systematic examination. This study examines AI implementation forms, impacts, and ethical implications in elementary education through systematic literature review. Following PRISMA guidelines, 16 articles published between 2020-2025 were analyzed from Google Scholar, Springer, ScienceDirect, and Taylor & Francis databases. PICO framework guided inclusion/exclusion criteria focusing on AI implementation in elementary schools and ethical considerations. AI implementation encompasses personalized content delivery systems, analytics-based student management, and pedagogical strategies utilizing diverse tools (chatbots, intelligent tutoring systems, educational robots). Positive impacts include enhanced student motivation, creativity, engagement, and teaching efficiency. However, significant concerns emerged regarding algorithmic bias, privacy violations, technological dependency, academic integrity, and digital divide. Critically, ethical frameworks remain inadequately integrated into elementary curricula, creating vulnerabilities for young learners.  Successful AI integration requires comprehensive approaches addressing teacher preparation, structured ethical education, clear institutional policies, and equity-oriented strategies. Educational leaders must adopt ethical leadership prioritizing student privacy, algorithmic fairness, and educational justice. Future research should employ longitudinal and experimental designs across diverse contexts to develop evidence-based frameworks for ethically-informed AI implementation in elementary education.